(untitled) (Journal of Global Accounting, 2025)
The integration of disruptive technologies such as artificial intelligence (AI), blockchain, and big data analytics into accounting practices has revolutionized the field, offering significant benefits in terms of efficiency, transparency, and decision-making. However, these advancements also present substantial ethical challenges that must be addressed to ensure responsible adoption. This study explores the ethical implications of these technologies in accounting, focusing on transparency, accountability, fairness, data privacy, and security. Through a comprehensive synthesis of insights from existing literature and case studies, the research identifies key ethical concerns and proposes guidelines and best practices for their mitigation. The findings highlight the importance of developing transparent AI systems that are explainable to stakeholders, establishing clear accountability mechanisms for AI-driven decisions, and implementing strategies to mitigate biases in AI algorithms. The study also underscores the need for robust data privacy and security measures in the use of blockchain technology, particularly in compliance with data protection regulations such as the General Data Protection Regulation (GDPR). Additionally, the research emphasizes the necessity of ethical training and education for accounting professionals, fostering collaboration and stakeholder engagement, and regularly monitoring and evaluating ethical practices. By addressing these ethical considerations, the accounting profession can navigate the challenges associated with disruptive technologies and harness their benefits responsibly. The recommendations provided in this study aim to guide the ethical adoption and implementation of AI, blockchain, and big data analytics in accounting, ensuring that these technologies contribute positively to the profession and society at large.